Cognitive features of the concept food in Russian, English and Chinese linguocultures - Xu, Yidan (Linguistics and Culture Review, 2021)
The article is devoted to the similarities and differences of the concepts YEDA / FOOD / SHI in Russian, English, and Chinese linguocultures. The purpose of the work is to present semantics structures of the concept FOOD in named languages and analyze them using the comparative method. The research was performed on the basis of explanatory and phraseological dictionaries of Russian, English and Chinese languages. The results prove that the general idea of the concept differs in the Russian, English, and Chinese linguocultures, which comes down to its subjects, functions, and forms. The transferred meanings of the verbalizers food and yeda remain close to their direct meanings, and the corresponding concepts possess only positive connotations, while the meanings of the verbalizer shi are more diverse, and the corresponding concept possesses ambivalent connotations. Besides, cognitive features related to the studied concepts are more pronounced in the Chinese linguoculture.